Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1039/a909375c
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the diffusion coefficient of nickel nitrate in wet silica gel using UV/VIS spectroscope equipped with a flow cell

Abstract: A novel technique for the measurement of the di †usion coefficient of a solute in a transparent wet-gel monolith was developed by analyzing the decay behavior of the absorbance of the gel plate in a Ñow cell. The di †usion coefficient of a in a wet silica gel is estimated by Ðtting the absorbanceÈtime data with an Ni(NO 3 ) 2 exponential function. The efficiency of the technique was ensured by testing the e †ects of several measurement conditions, such as the Ñow rate of the external solution and the thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…This was further confirmed by UV/Vis monitoring of the tert-butanol supernatant collected after thermal treatment of the PtNiNC-NGA, where oxidized Ni can be detected (Figure S12). [18] The loading of PtNiNFs on the PtNiNF-NGAs can be adjusted by controlling the concentration of the metal precursors in the mixed solution, where the RGO was immersed into.B esides the PtNiNF-NGA discussed above with 8.0 wt %Pt, PtNiNF-NGAs with 5.2 wt %a nd 19.4 wt %P tl oadings can be also easily obtained (Figure S13). Further systematic investigations indicate that the initial ratio between the Ni precursor and Pt precursor has great influence on the final PtNi structure.T he PtNiNF-NGA was prepared using aN i/Pt precursor ratio of 1.0:1.3.…”
Section: Resultsmentioning
confidence: 99%
“…This was further confirmed by UV/Vis monitoring of the tert-butanol supernatant collected after thermal treatment of the PtNiNC-NGA, where oxidized Ni can be detected (Figure S12). [18] The loading of PtNiNFs on the PtNiNF-NGAs can be adjusted by controlling the concentration of the metal precursors in the mixed solution, where the RGO was immersed into.B esides the PtNiNF-NGA discussed above with 8.0 wt %Pt, PtNiNF-NGAs with 5.2 wt %a nd 19.4 wt %P tl oadings can be also easily obtained (Figure S13). Further systematic investigations indicate that the initial ratio between the Ni precursor and Pt precursor has great influence on the final PtNi structure.T he PtNiNF-NGA was prepared using aN i/Pt precursor ratio of 1.0:1.3.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption spectrum of film 1 showed a shoulder peak at 380 nm, which is attributed to nickel nitrate (Ni 2+ ion). 7), 8) This peak disappeared for the film 2 after 60 min UV irradiation, and the film color turned from green (film 1) to pale brown (film 2). The resulting film color was close to the observed color for nickel oxide-based films reported previously.…”
Section: Resultsmentioning
confidence: 96%
“…These values are about 60% of diffusion coefficient of respective bulk solution due to the effect of pore structures. The initial and boundary conditions of diffusion during washing of the gel are essentially the same as those in the measurement of D in our previous work [27]. Therefore, the average concentration, C av , of sodium nitrate in the gel can be described with…”
Section: Effect Of the Presence Of Sodium Ionmentioning
confidence: 95%
“…Previously, we have measured diffusion coefficient, D, of nickel nitrate in a wet silica gel and have found that it is about 6 · 10 À10 m 2 s À1 [27,28]. D of sodium nitrate in a wet gel was also reported to be %10 · 10 À10 m 2 s À1 [29].…”
Section: Effect Of the Presence Of Sodium Ionmentioning
confidence: 95%
See 1 more Smart Citation